Use of Methotrexate for More Than 4 Years Is Not Associated with Liver Fibrosisin Rheumatoid Arthritis Patients - Tati Muliani (Indonesian Rheumatology Associantion, 2023)
v Background. Methotrexate is an anchor drug in the management ofrheumatoid arthritis (RA). However, the association between methotrexateand development of liver fibrosis remains a subject of controversy. Non invasivemethodstoassessliverfibrosis, such as the FIB-4 score, have beendeveloped. RA patients on methotrexate therapy should be monitored for anysigns of liver fibrosis. This study aims to investigate the correlation betweenmethotrexate cumulative dose and the FIB-4 score in rheumatoid arthritispatients who received methotrexate therapy to assess the hepatotoxic effectsof methotrexate. Methods. This cross-sectional study involved rheumatoidarthritis patients who received methotrexate therapy at Dr. Hasan SadikinGeneral Hospital Bandung from September 2022 to November 2022. Clinicaldata, laboratory tests (including platelet values and liver function test), andcumulative methotrexate doses were extracted from medical records. Datawere analyzed using the Spearman correlation test. Results. This studyinvolved 100 subjects aged between 22-82 years, comprising 93% women and7% men. The median FIB-4 score was 0.73 (0.24-6.80), while the medianmethotrexate cumulative dose was 2477.5 mg, with a range of 1005-10400mg. The results showed that correlation coefficient between the FIB-4 scoreand methotrexate cumulative dose in rheumatoid arthritis patients was 0.089 (p=0.378).Conclusion.There is no significant correlation between FIB 4score and cumulative dose of methotrexate inrheumatoid, arthritis, patients. The use of methotrexate in RA patientsover 4 years is relativelysafe as it does not increase the risk of liver fibrosis.